If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + 12 = 6v Reorder the terms: 12 + 3v = 6v Solving 12 + 3v = 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 12 + 3v + -6v = 6v + -6v Combine like terms: 3v + -6v = -3v 12 + -3v = 6v + -6v Combine like terms: 6v + -6v = 0 12 + -3v = 0 Add '-12' to each side of the equation. 12 + -12 + -3v = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3v = 0 + -12 -3v = 0 + -12 Combine like terms: 0 + -12 = -12 -3v = -12 Divide each side by '-3'. v = 4 Simplifying v = 4
| (2x-4)-12=4x-15 | | X^2+1x+1.5=0 | | -5x-8=48 | | (2x+4)-12=4x-15 | | -6h+5=5-6h | | 2z/24=6/8 | | 4x=-17 | | 2=2(x+3) | | 2x+6=6x-18 | | y-(-11)=-15 | | 15-10y=21 | | -16=x-72 | | -1+m=16 | | 13y+22=16.6 | | m-13=-8 | | y+(-18)=-37 | | 3x-(2x-6)=2 | | 3x-10x+15=20 | | 6y+12=5y | | 4x+2=10x-12 | | 8(3m-7)=32 | | -n+5+3n=15 | | y^3+49y=0 | | 4+2X-12x=0 | | -4+-2x=-3x-12 | | 12-2(n-2)=-2 | | -2x+13=-5x+21 | | 2x-2x+4=0 | | -3x-2x=-4-12 | | 2x+10x=0 | | -7y+3=21 | | 2x-5x+4=0 |